Tingkat Kecemasan Pada Pasien Preoperasi Sectio Caesarea di Rumah Sakit Mardi Rahayu Kudus - Anita Novi Kristanti; Noor Faidah (Universitas Ngudi Waluyo, 2022)
Patients who willundergo surgical procedures such as sectio caesarea. Will cause an emotional reaction, such as prooperative anxiety. In Indonesia, based on the results of Basic Health Research in 2018, the prevalence of sectio caesarea in childbirth was 17.6%, the highest in the DKI Jakarta area (31,3%) and the lowest in Papua (6,7%). While the method of delivery by sectio caesarea in Central Java reached (17,1%). At Mardi Rahayu Kudus Hospital from 2016-2020, data on the number of sectio caesarea were obtained the highest was in 2017 which was 1.523 cases.The operation caused anxiety in presurgery sectio caesarea patients. This research aims to determine the level of anxiety in presurgery sectio caesarea patients at Mardi Rahayu Hospital Kudus. This type of research is descriptive using a cross sectional approach. The population is all presurgery patients who will undergo sectio caesarea surgery at the Mardi Rahayu Kudus Hospital. The sampling technique of this research was purposive sampling with a total sample of 30 respondents. The data analysis technique is univariate The results of the univariate analysis of the anxiety level of presurgery sectio caesarea at Mardi Rahayu Hospital in 30 respondents, no anxiety 2 respondents (6.7%), mild anxiety 11 respondents (36.7%), moderate anxiety 16 respondents (53.3%) , and severe anxiety 1 respondent (3.3%). It is hoped that it can provide intervention through education and information to patients who will undergo sergery.AbtsrakPasien yang akan menjalani prosedur operasi seperti sectio caesarea. Akan menimbulkan reaksi emosional, seperti kecemasan prooperatif. Di Indonesia, berdasarkan hasil Riset Kesehatan Dasar tahun 2018, prevalensi sectio caesarea pada persalinan sebesar 17,6%, tertinggi di wilayah DKI Jakarta (31,3%) dan terendah di Papua (6,7%). Sedangkan cara persalinan dengan sectio caesarea di Jawa Tengah mencapai (17,1%). Di RS Mardi Rahayu Kudus dari tahun 2016-2020 didapatkan data jumlah sectio caesarea tertinggi pada tahun 2017 yaitu sebanyak 1.523 kasus. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan pada pasien prabedah sectio caesarea di RSUD Mardi Rahayu Kudus. Jenis penelitian ini adalah deskriptif dengan menggunakan pendekatan cross sectional. Populasi adalah seluruh pasien prabedah yang akan menjalani operasi sectio caesarea di RS Mardi Rahayu Kudus. Teknik pengambilan sampel penelitian ini adalah purposive sampling dengan jumlah sampel sebanyak 30 responden. Teknik analisis data adalah univariat Hasil analisis univariat tingkat kecemasan praoperasi sectio caesarea di RS Mardi Rahayu pada 30 responden, tidak ada kecemasan 2 responden (6,7%), kecemasan ringan 11 responden (36,7%), kecemasan sedang 16 responden (53,3%), dan kecemasan berat 1 responden (3,3%). Diharapkan dapat memberikan intervensi melalui edukasi dan informasi kepada pasien yang akan menjalani operasi.